Proyecto de inversión para la comercialización de productos elaborados de algarrobo como una nueva línea de producto para la universal s.a. - Briones Carrión, Tatiana Valeria (2010)
This project is a market research and financial feasibility for the implementation of a new line of products made of carob in La Universal SA It seeks to tap business opportunities generated by the high demand for organic products, healthy and with fewer calories, among these, carob (chocolate substitute), the one is not being fully exploited by producers despite the fact of the existing cropsp and an being a very helpful tree, with a high nutritional value for health, so the proposal to the company La Universal (Universal Sweet Industries) it’s to make a new line of products that will improve carob participation in the market and consequently increase the profits of the company. The study includes an analysis of financial viability that details the costs involved in introducing these products, considering existing machinery. The revenue to be obtained and thus, with criteria based on financial and market research, the appropriateness of the project